Analisis Kepuasan dan Loyalitas Konsumen Produk Tela-Tela Barokah Depan Kampus Baru Universitas Halu Oleo pada Masa Covid-19 - Rustiani, Rustiani; Salam, Idrus; Limi, Muhammad Aswar (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
This study aims to determine consumer satisfaction and loyalty of late-late products during the Covid-19 periodâ€”this research at the Barokah Tela-tela business in front of the new UHO campus using 30 respondents. Determination of respondents is done by accident (Accidental sampling), assuming that the respondent can be trusted. The variables observed in this study were consumer characteristics, tela-tela, and customer satisfaction and loyalty and satisfaction analysis methods using Customer Satisfaction Index (CSI) analysis and loyalty analysis using committed buyers, like the brand, satisfied buyers, habitual buyers, and switches. Buyers. The results show that the calculation of customer satisfaction analysis of the Customer Satisfaction Index is 0.77 or 77.46%. The CSI value criterion states that the vulnerable value of 0.66-0.80 is a satisfied consumer criterion. Based on this situation, it can be concluded that Barokah consumers have shown a satisfying attitude towards the products they consume. The survey results show that the most consumers who state that they are satisfied are the taste and cleanliness attributes of the Tela Barokah business location. The results of the calculation of consumer loyalty analysis using switcher buyer analysis are 53.33%, chronic is 79.33%, the satisfied buyer is 72.00%, liking the brand is 76.67%, and committed buyer is 62.00%. The analysis results are mainly in the index interval of 61.00-80.00, which means that Barokah consumers have shown a loyal attitude. The existence of the Covid-19 pandemic did not hurt the decline in consumer demand for snack products in the business. This is known from the income that remains in the range of Â± IDR400.000 - IDR1.500.000 - every day both before and during the Covid-19 outbreak in Kendari City.